Study about Genius Ideas and Genius Mistakes: Non-Material Nature of the Psyche, Part II - Reshetnikov, Mikhail (Research Developments in Arts and Social Studies Vol. 1, 2022)
The author develops ideas, which he presented in his paper What is the Psyche? What are we Curing? and critically analyses works by Descartes, I.M. Sechenov and I.P. Pavlov, which determined our methods of studying the psyche and treating mental disorders for many centuries. Reflexes of the Brain by I.M. Sechenov and ideas of the second signal system and higher nervous activity by I.P. Pavlov are analysed in detail. The author proves that these ideas, which still influence development of psychology, psychiatry, psychotherapy and social sciences, are fallacious. The psyche is a non-material informational structure that develops in result of language programming of the brain in a social informational environment; it is the highest regulator of cognitive, emotional, behavioural and ideomotor acts, that is of social adjustment of personality in general, in accordance with requirements for language and culture in a specific society, which influence the development of the psyche.